Ultrasonic strategies for mitigating microbial adhesion and biofilm formation on medical surfaces: a mini review - Huang, Jie; Fu, Qiang; Shao, Xingang; Li, Yuanzhe (Frontiers in Microbiology, 2025)
Biofilm formation on medical surfaces poses significant challenges, leading to compromised device functionality and an increased risk of infections. Addressing this issue requires effective strategies that balance efficacy with safety. This mini-review examines the application of ultrasound as a promising approach for biofilm control in medical contexts. Drawing from recent studies, it explores the mechanisms by which ultrasound disrupts biofilms, highlighting its ability to break down extracellular polymeric matrices and enhance the efficacy of antimicrobials. The review also discusses practical considerations, including ultrasound parameter optimization, biocompatibility, and integration with other anti-biofilm strategies. While ultrasound has demonstrated potential in disrupting biofilms, further research is essential to refine these approaches, improve treatment outcomes, and ensure compatibility with medical applications. By advancing our understanding and application of ultrasonic techniques, this field holds promise for improving patient safety and enhancing medical device longevity.